An Analysis of Students’ Ability in Comprehending TOEFL Reading Test at English Department Universitas Negeri Padang - Annisa Kurniawati; Fitrawati Fitrawati (Journal of English Language Teaching, 2020)
This research was about the students' ability in comprehending TOEFL reading test at at English department of Universitas Negeri Padang. The research design was the descriptive research. The population of this study was third year students of English Education Study Program Academic Year 2017. The population was 148 students from 6 classes. The sample was taken by cluster random sampling technique so that the number of samples obtained was 22 samples. The instrument used was a reading TOEFL test for 60 minutes. The students’ comprehension ability was also analyzed in 5 types of reading comprehension skill. Based on this research, students' ability in comprehending TOEFL reading texts was poor. This finding indicated that the third-year students at English Department of UNP had less comprehension in reading TOEFL test.